Not Lower-Limb Joint Strength and Stiffness but Vertical Stiffness and Isometric Force-Time Characteristics Correlate With Running Economy in Recreational Male Runners - Zhang, Qin; Nassis, George P.; Chen, Shiqin; Shi, Yue; Li, Fei (Frontiers in Physiology, 2022)
Neuromuscular characteristics, such as lower-limb joint strength, the ability to reuse elastic energy, and to generate force are essential factors influencing running performance. However, their relationship with running economy (RE) remains unclear. The aim of this study was to evaluate the correlations between isokinetic lower-limb joint peak torque (PT), lower-limb stiffness, isometric force-time characteristics and RE among recreational-trained male runners. Thirty male collegiate runners (aged 20–22 years, VO2max: 54.02 ± 4.67 ml·kg-1·min-1) participated in test sessions on four separate days. In the first session, the body composition and RE at 10 km·h-1 were determined. In the second session, leg and vertical stiffness (Kleg and Kvert), knee and ankle stiffness (Kknee and Kankle) were evaluated. In the third session, isokinetic knee and ankle joint PT at velocity of 60°·s-1 were tested. The force-time characteristics of isometric mid-thigh pull (IMTP) were evaluated in the final session. The Pearson’s product-moment correlations analysis shows that there were no significant relationships between knee and ankle joint concentric and eccentric PT, Kknee and Kankle, Kleg, and RE at 10 km·h-1. However, Kvert (r = -0.449, p < 0.05) and time-specific rate of force development (RFD) for IMTP from 0–50 to 0–300 ms (r = -0.434 to -0.534, p < 0.05) were significantly associated with RE. Therefore, superior RE in recreational runners may not be related to knee and ankle joint strength and stiffness. It seems to be associated with vertical stiffness and the capacity to rapidly produce force within 50–300 ms throughout the lower limb.